2022
DOI: 10.3390/jcm11113041
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Thyroxine Concentration and Lithium Intoxication—An Analysis Based on the LiSIE Retrospective Cohort Study

Abstract: (1) Background: It has been suggested that hyperthyroxinaemia is a risk factor for lithium intoxication by altering tubular renal function. (2) Methods: We determined the relevance of hyperthyroxinaemia as a risk factor for lithium intoxication in patients with bipolar or schizoaffective disorder in the framework of the LiSIE (Lithium-Study into Effects and Side Effects) retrospective cohort study. Of 1562 patients included in the study, 897 patients had been exposed to lithium at any time between 1997 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This makes it difficult to derive an incidence rate for lithium intoxications requiring intensive care. Using our own LiSIE cohort with a time frame from 1997 to 2017, we found an incidence rate of 9.7/1,000 PY for unintended lithium intoxications ( 33 ). In previous work exploring the LiSIE cohort from 1997 to 2013, we found that of 91 identified events of lithium intoxication including overdoses, 34% required intensive care.…”
Section: Discussionmentioning
confidence: 98%
“…This makes it difficult to derive an incidence rate for lithium intoxications requiring intensive care. Using our own LiSIE cohort with a time frame from 1997 to 2017, we found an incidence rate of 9.7/1,000 PY for unintended lithium intoxications ( 33 ). In previous work exploring the LiSIE cohort from 1997 to 2013, we found that of 91 identified events of lithium intoxication including overdoses, 34% required intensive care.…”
Section: Discussionmentioning
confidence: 98%
“…The current work is the second in series within LiSIE exploring the relationship between hyperthyroid states and lithium. Whereas the first study examined the relationship between hyperthyroxinaemia, that is, increased free thyroxine (fT4) and lithium intoxication, 16 the current work examines the relationship between hyperthyroidism and history of lithium exposure. We have described the method in detail in the first study.…”
Section: Methodsmentioning
confidence: 99%
“…We have described the method in detail in the first study. 16 To ease understanding, we described the method in detail even here. We have summarised the whole method in a STROBE checklist (Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation